Dense pure binderless WC bulk material prepared by spark plasma sintering. (14th November 2015) - Li, S. K.; Li, J. Q.; Li, Y.; Liu, F. S.; Ao, W. Q.
Abstract : The phases, microstructures and mechanical properties of binderless WC bulk materials prepared by the spark plasma sintering technique were investigated systematically. The addition of carbon was added to eliminate the impurity phase W2 C. The relative density, Vickers hardness and grain size increase obviously with increasing sintering temperature, but increase weakly with increasing pressure or sintering time. The high relative density of 99·1%, HV30 of 27·5 GPa and fracture toughness K IC of 4·5 MPa m 1/2 of pure binderless WC bulk with a grain size of 400 nm was obtained by sintering the WC powders with a particle size of 200 nm and the addition of 0·63 wt-%C at 1800°C for 6 min under 70 MPa.